Laser and TIG welding of additive manufactured Ti-6Al-4V parts - KURT, MUSTAFA; ŞEN, MURAT (My University, 2022)
Electron beam melting (EBM) is a powder bed additive manufacturing (AM) technology for small and medium-sized Ti-6Al-4V components. In this study, EBM-built Ti-6Al-4V tensile specimens were joined using tungsten inert gas (TIG) welding and laser beam welding (LBW) to form large-scale components. Weld morphology, defects, mechanical properties, and microstructure of joints made by LBW and TIG welding were compared. It was found that the pore sensitivity of EBMed Ti-6Al-4V is extremely high. In EBM, the most common defect is pores, but this has been ignored as parts are broken at welding zone. Large pores are distributed along the edge of the weld in TIG welding, whereas in laser welding they are distributed at top of the weld. LBW has a much smaller grain size in the weld center than TIG welding. The TIG welded sample has more heat at the weld boundary. Mechanical properties of TIG welded parts were superior to laser welded parts. The main reason for this is that the weld cross section is larger than the center. In addition, in the microstructure examination of TIG welding, it was observed that the weld had fewer defects than laser welding. Also, the elongation of all specimens is very low.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KARAKTERİZASYON VE TEST; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CHARACTERIZATION & TESTING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; electron beam melting (EBM); laser welding; mechanical properties; Ti-6Al-4V alloy; tungsten inert gas welding; BEAM MELTED TI-6AL-4V; MECHANICAL-PROPERTIES; SINGLE TRACKS; MICROSTRUCTURE; ALSI10MG; BEHAVIOR; TEXTURE; ALLOY